1998
DOI: 10.1177/135676679800400306
|View full text |Cite
|
Sign up to set email alerts
|

The role of tour operators' promotional material in the formation of destination image and consumer expectations: The case of the People's Republic of China

Abstract: Image formation has been seen as important in destination marketing. However, image formation and development is a complex process that is intricately entwined with the destination selection process. A variety of sources helps to form the image of a destination in the mind of a potential holidaymaker. Similar factors will also influence consumer expectations. This paper uses the People's Republic of China as an example, and explores the role tour operators play in creating and developing image and expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 14 publications
1
22
0
2
Order By: Relevance
“…"Content analysis has occupied a privileged position in the social sciences as a method for studying photographic media" (Albers & James, 1988: 145), being used by a great number of authors to analyse destination image (Dilley, 1986;Camprubí, Guia & Comas, 2012;Pritchard & Morgan, 1995, 1996Santos, 1998;Galí & Donaire, 2005;Govers & Go, 2005;Choi, Letho & Morrison, 2007). Generally, a categorisation is used in order to systematise content analysis, and a set of suitable parameters and rules established to maintain congruency and validity of data (Albers In this study, four categories were used to classify pictures based on previous research (Camprubí et al, 2012;Dilley, 1986;Donaire & Galí, 2011;Galí & Donaire, 2005;Govers & Go, 2005;Pritchard & Morgan, 1995;Santos, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…"Content analysis has occupied a privileged position in the social sciences as a method for studying photographic media" (Albers & James, 1988: 145), being used by a great number of authors to analyse destination image (Dilley, 1986;Camprubí, Guia & Comas, 2012;Pritchard & Morgan, 1995, 1996Santos, 1998;Galí & Donaire, 2005;Govers & Go, 2005;Choi, Letho & Morrison, 2007). Generally, a categorisation is used in order to systematise content analysis, and a set of suitable parameters and rules established to maintain congruency and validity of data (Albers In this study, four categories were used to classify pictures based on previous research (Camprubí et al, 2012;Dilley, 1986;Donaire & Galí, 2011;Galí & Donaire, 2005;Govers & Go, 2005;Pritchard & Morgan, 1995;Santos, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a categorisation is used in order to systematise content analysis, and a set of suitable parameters and rules established to maintain congruency and validity of data (Albers In this study, four categories were used to classify pictures based on previous research (Camprubí et al, 2012;Dilley, 1986;Donaire & Galí, 2011;Galí & Donaire, 2005;Govers & Go, 2005;Pritchard & Morgan, 1995;Santos, 1998). These categories were nature, heritage, culture and tourist services (see Table 1 for detailed descriptions), and were chosen on the basis of two criteria: firstly, they were four of the most common categories for analysing tourism image; and secondly, they are the four categories that include the main tourist characteristics of the destination used as a case study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is now an axiom that all marketing communications should reinforce the brand identity. There has been little research building on early work by Lawton and Page (1997), Santos (1998) and Gartner and Bachri (1999) The relationship between advertising and sales has yet to be established in the marketing literature (see Schultz & Schultz, 2004), and so it should not be surprising that this represents another important gap in the destination marketing literature. A number of studies have concluded the link between destination advertising and tourist receipts was tenuous (see for example Faulkner, 1997, p. 27).…”
Section: Destination Brand Positioningmentioning
confidence: 99%
“…Examples of this include the prevailing age-discrimination found in tourist brochures, which repeatedly focus on young to middle-aged travellers whilst neglecting senior travellers in the pictures employed [22,23]. Other examples highlight the often male-dominated heterosexual-framework brochures confine themselves to [24][25][26][27][28][29]; the promotion linked to nation building [24,[30][31][32][33][34]; and the dominant Caucasian perspective that is found in tourist brochures [5,6,[35][36][37].Not only written text has been analysed in terms of the messages communicated.Pictures and films are equally filled with narratives that shape tourists' perceptions.Albers and James [38] did a thorough investigation of pictures on postcards depicting ethnic minorities in America. They outlined a methodology for how photographs can be used to investigate tourist practice as well as stereotypes born through recurring themes in travel photography.…”
mentioning
confidence: 99%